2004
DOI: 10.1016/j.femsim.2004.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Exploration ofMoraxella catarrhalisouter membrane proteins, CD and UspA, as new carriers for lipooligosaccharide-based conjugates

Abstract: Moraxella catarrhalis outer membrane proteins, CD and ubiquitous surface protein A (UspA), were used as carriers for M. catarrhalis detoxified lipooligosaccharide (dLOS)-based conjugates. Our study was designed to investigate the feasibility of CD and UspA as protein carriers for dLOS-based conjugates and their possible synergic effects on protection from both anti-LOS and anti-CD or anti-UspA antibody responses. Female Balb/c mice were immunized subcutaneously three times with dLOS-CD or dLOS-UspA conjugate i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…Our current bactericidal assay revealed that 50 to 65% of the BALB/c mouse antisera elicited by the conjugates plus Ribi adjuvant showed bactericidal activity against the homologous type B strain. This result is partially consistent with type A dLOS-protein conjugates, where 45% of outbred mouse antisera and up to 100% of BALB/c mouse antisera showed bactericidal activity (21,29). It is not clear if the dif- ference is due to different LOS serotypes, protein carriers, mouse strains, or the assays themselves.…”
Section: Discussionmentioning
confidence: 53%
“…Our current bactericidal assay revealed that 50 to 65% of the BALB/c mouse antisera elicited by the conjugates plus Ribi adjuvant showed bactericidal activity against the homologous type B strain. This result is partially consistent with type A dLOS-protein conjugates, where 45% of outbred mouse antisera and up to 100% of BALB/c mouse antisera showed bactericidal activity (21,29). It is not clear if the dif- ference is due to different LOS serotypes, protein carriers, mouse strains, or the assays themselves.…”
Section: Discussionmentioning
confidence: 53%
“…We showed that antibodies derived in this way were bactericidal and protective against wild-type N. meningitidis strains [10]. Previous studies on LPS based vaccines to combat M. catarrhalis have been carried out in the laboratories of Gu [13][14][15][16][17][18][19]. This elegant research has documented that it is indeed possible to raise bactericidal antibodies to M. catarrhalis following immunisation with LPS-based glycoconjugates.…”
Section: Introductionmentioning
confidence: 88%
“…The CD outer membrane protein of M. catarrhalis has been identified as a potential vaccine against Moraxella infection (9,26) and is a safe and effective carrier for M. catarrhalis detoxified lipooligosaccharide (LOS)-based conjugates (18). Serum immunoglobulin G (IgG) antibodies specific to CD are present in infants with otitis media (25) and in children with otitis media with effusion (11).…”
mentioning
confidence: 99%